Optimum Fiber Content to Improve Compressive Strength of Glass Fibers Reinforced Cellular Lightweight Concrete for Hollow-core Precast Panel Walls - Loyjaroen, Phakin; Puttala, Songrit; Kaewkulchai, Griengsak (Indochina Applied Sciences, 2025)
This study aimed to identify the optimal amount of glass fibers to enhance the compressive strength of Glass Fiber reinforced Cellular Lightweight Concrete (GF-CLC). The compressive strength of cellular lightweight concrete with densities of 1.20 × 102 kg m–3 and 1.60 × 102 kg m–3, containing different percentages (1%, 2%, 3%, 4%, 5%, and 6% by weight of cement) of glass fibers, was evaluated using BS EN 12390 Part 1 – 4 tests and compared with non-fiber specimens. The results indicate that 1% glass fiber reinforcement has an insignificant effect on compressive strength, while proportions of 2 – 4% by weight of cement lead to a significant increase in compressive strength at all stages of curing age. The optimum fiber content was found to be 4% by weight of cement, resulting in compressive strength improvements of 2 times and 1.60 times compared to non-fiber reinforced specimens at 1.20 × 102 kg m–3 and 1.60 × 102 kg m–3, respectively. However, adding more than 4% glass fiber by weight of cement leads to a decrease in compressive strength and a constant tendency at higher densities. Compressive strength tends to increase with increased density, curing time, and fiber content because more dense concrete provides higher bonding and pull-out strength between CLC and glass fiber, thereby enhancing the fiber’s performance in resisting tensile and shear forces in the cellular lightweight concrete particles, resulting in higher ultimate compressive strength.